Analisis Komparatif Penerapan Suku Bunga KPR Bank di Batam - Johny Budiman; Yenny Fyfy Susanty (Jurnal Manajemen Maranatha, 2014)
Abstract: This study analyzes each of the interest calculation method which used on bank loans, consist of flat, effective (sliding), and annuitiesmethod, as well as murabahah in Islamic bank, along with the comparison in cases. The results found that with the same interest rate, the amount of interest charged on a flat method is the most expensive, followed by annuities then effective method with the ratio 1,79:1:1,097 (flat, effective, and annuities). As for the comparison with murabahah is in term of the risk of the interest rate fluctuations. The level of profit margins (calledinterest on conventional banks) on murabahah is fixed until the end of the credit period, while interest on conventional bank loans tend to be floating (changes according to the BI rate). In the condition of stable BI rate, the results showed thatthe ratio of commercial bank interest and Islamic banks margins are 1 : 1,38, which is margin in Islamic banks is higher.Keywords: interest rate methods, annuity, flat rate, effective rate, bank loan, KPR, banking, Islamic bank, murabahah